Risk factors for pneumonia among patients with Parkinson's disease: a Taiwan nationwide population-based study - Chang YP (Dove Medical Press, 2016)
Yang-Pei Chang,1 Chih-Jen Yang,2 Kai-Fang Hu,3 A-Ching Chao,4 Yu-Han Chang,5 Kun-Pin Hsieh,6 Jui-Hsiu Tsai,7 Pei-Shan Ho,8,9 Shen-Yang Lim101Department of Neurology, 2Department of Internal Medicine, 3Department of Dentistry, Kaohsiung Municipal Ta-Tung Hospital, 4Department of Neurology, College of Medicine, 5Department of Management, Kaohsiung Municipal Ta-Tung Hospital, 6School of Pharmacy, College of Pharmacy, 7Department of Psychiatry, Kaohsiung Municipal Ta-Tung Hospital, 8Faculty of Dental Hygiene, College of Dental Medicine, Kaohsiung Medical University, 9Cancer Center, Kaohsiung Medical University Chung-Ho Memorial Hospital, Kaohsiung, Taiwan, Republic of China; 10Faculty of Medicine, University of Malaya, Kuala lumpur, MalaysiaObjective: Pneumonia is the leading cause of death in patients with Parkinson’s disease (PD). However, few studies have been performed to explore the risk factors for pneumonia development in patients with PD.Methods: We conducted a nationwide population-based cohort study of patients with PD to identify the risk factors for these patients developing pneumonia. Participants with newly diagnosed PD between 2000 and 2009 were enrolled from the 2000–2010 National Health Insurance Research Database in Taiwan. We compared patients with PD with an incidence of hospitalization with pneumonia vs those without, and Cox proportional hazard models were used to estimate the risk of pneumonia.Results: Of the 2,001 enrolled patients (mean follow-up duration 5.8 years, range: 2.7–14.7 years), 381 (19.0%) had an incidence of hospitalization with pneumonia during the study period. Multivariate Cox proportional hazards analysis identified older age group (≥80 years of age, hazard ratio [HR] =3.15 [95% confidence interval 2.32–4.28]), male sex (HR =1.59 [1.29–1.96]), certain geographic regions (northern, HR =1.36 [1.04–1.78], southern and eastern, HR =1.40 [1.05–1.88]), rural areas (HR =1.34 [1.05–1.72]), chronic heart failure (HR =1.53 [1.02–2.29]), and chronic kidney disease (HR =1.39 [1.03–1.90]) as risk factors for hospitalization with pneumonia in patients with PD. However, treatment for dental caries was a protective factor (HR =0.80 [0.64–0.99]).Conclusion: The results of this study highlight risk factors that are associated with hospitalization with pneumonia, and, for the first time, suggest a link between treated dental caries and a diminished risk of hospitalization with pneumonia in patients with PD.Keywords: pneumonia, Parkinson’s disease, dental caries, chronic heart failure, chronic kidney disease